Evaluation of Zein Nanoparticles as Delivery Agents of SARS-CoV-2 Antigens - Verónica Araceli Márquez-Escobar; María José Alonso-Cerda; Sergio Rosales-Mendoza; María de Lourdes Betancourt-Mendiola (Vaccines, 2025)
Background/Objectives: Nanovaccines have significant potential to enhance immunization strategies by improving efficacy, safety, and cost-effectiveness. In particular, organic nanoparticles hold promise for the generation of low-cost nanovaccines obtained by environmentally friendly methods. In this study, the feasibility of using zein nanoparticles (NPs) as carriers for an antigenic peptide (p30) and the receptor binding domain (RBD) from SARS-CoV-2 spike protein was explored. Methods: A synthesis method for zein NPs was established by combining previously reported techniques, and the resulting NPs were characterized in terms of morphology, particle size, polydispersity index (PDI), surface charge, and colloidal stability using dynamic light scattering (DLS) and transmission electron microscopy (TEM). Tween 20 was employed as a surfactant to enhance particle stability and prevent aggregation. Results: The zein NPs were deemed safe based on an in vitro cytotoxicity assay using Vero cells. Immunogenicity assessments demonstrated that zein NPs:p30 and zein NPs:RBD induced IgG responses in test mice, whose magnitude was comparable to those achieved with alum as an adjuvant. Conclusions: These findings support the use of zein NPs as promising vaccine delivery vehicles with adjuvant effects due to their ease and environmentally friendly synthesis, high stability, and low cost.